FEASIBILITY STUDY OF USING A SINGLE- PHASE Z-SOURCE INVERTER IN PHOTOVOLTAIC SYSTEMS - Konjedic, Tine; Truntič, Mitja; Milanovič, Miro (Journal of Energy Technology, 2024)
This paper presents a single-phase Z-source inverter intended to be used in grid-connected photovoltaic systems. The Z-source inverter is a single-stage converter that has buck-boost features. The operation principle of this converter was analyzed by using equivalent circuits during shoot-through and non-shoot-through states. For these states, voltage conditions were described with mathematical equations. Two types of pulse-width modulation (PWM) were proposed as well as verified and tested with simulation in Matlab/Simulink software. A control scheme was presented with the purpose of placing a Z-source inverter in a grid-connected photovoltaic system.